Exploring the Impact of Self-Control, Motivation, and Resilience on Students' Self-Compassion - Apsari, Diani Akmalia; Atmoko, Adi; Farida, Ika Andrini; Eva, Nur; Da Costa, Augusto; Fuadiyah, Aidah (Jurnal Kajian Bimbingan dan Konseling, 2024)
The core purpose of Pendidikan Profesi Guru Prajabatan (PPG) is to educate prospective teachers to become professional teachers. To achieve this goal, students requires psychological abilities when facing challenges such as dense and demanding tasks based on the curriculum that must be completed in 2 semesters. This study aims to (1) test the theoretical model of regression of self-compassion, and (2) determine the contribution of self-control, motivation, and resilience to self-compassion in PPG students. This study used a causal relationship design. Data were collected with (1) Brief Self Control Scale, (2) The Academic Motivation Scale, (3) The Connor-Davidson Resilience Scale, and (4) Self-Compassion Scale which have been tested for validity and reliability; data were analyzed with multiple regression. A total of 474 preservice PPG students participated. The results showed that theoretical model was fit. Self-control, motivation, and resilience have significant effects on self-compassion. This finding provides essential basis for policies to reinforce these three factors in enhancing self-compassion of PPG students. The toughness of the lectures and the immense challenges require self-compassion as a psychological support so that students are able to adapt and succeed in challenging tasks.